Are We Loyal To The Card Or To The Merchants? Factors Influencing Customer Loyalty In Multimerchant Loyalty Card Programs In Malaysia - Mustafa, Hasrina; Nordin, Dini Farahiyah (2015)
Loyalty program is a new generation of Customer Relationship Management (CRM) strategy and CRM is one of the vital aspects of the Integrated Marketing Communication (IMC). This study aims to understand the usage pattern of loyalty program among the cardholders and seek to examine factors influencing the customer loyalty in the multi-merchant loyalty card program in Klang Valley in terms of its perceived benefit, trust, commitment and satisfaction based on the main constructs of the Social Exchange Theory. Two levels of customers loyalty were examined namely the loyalty towards the program and the loyalty towards the merchants involved in the program. Data were collected from 230 cardholders of Bonuslink and BCard in Klang Valley, Malaysia via the online survey technique and data was analysed using descriptive analysis, Pearson Correlation and Multiple Regression analyses. Results of the Multiple Regression analysis showed that customer benefit, customer commitment and customer satisfaction are the best predictor variables of the customer loyalty towards the loyalty program. However, none of the independent variables were found to significantly predict the customers loyalty towards the merchants involved in the program, which further indicate greater customer loyalty towards the loyalty program not to the merchants.